1958
DOI: 10.1111/j.1476-5381.1958.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Substance P on the Peristaltic Reflex of the Isolated Guinea‐pig Ileum

Abstract: The introduction of substance P into the lumen of the isolated guinea-pig ileum caused an increase in the number and amplitude of the peristaltic waves. In preparations in which the peristaltic reflex was abolished, by fatigue, by external or internal application of 5-hydroxytryptamine, or by lowering the temperature of the bath, the introduction of substance P into the lumen of the intestine restored peristalsis. This effect of substance P was absent in preparations in which the mucous membrane was removed. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1960
1960
1989
1989

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The role of the mucosa and submucosa in initiating the peristaltic reflex is still not clear. According to Builbring, Lin & Schofield (1958) and Beleslin & Varagic (1958), destruction of the mucosa abolishes the peristaltic reflex in the ileum, while contrary results have been reported by Ginzel (1959a, b). Diament, Kosterlitz & McKenzie (1961) found that spontaneous shedding of the superficial layers of the mucosa during an experiment does not decrease the efficiency of the peristaltic reflex.…”
Section: Discussionmentioning
confidence: 87%
“…The role of the mucosa and submucosa in initiating the peristaltic reflex is still not clear. According to Builbring, Lin & Schofield (1958) and Beleslin & Varagic (1958), destruction of the mucosa abolishes the peristaltic reflex in the ileum, while contrary results have been reported by Ginzel (1959a, b). Diament, Kosterlitz & McKenzie (1961) found that spontaneous shedding of the superficial layers of the mucosa during an experiment does not decrease the efficiency of the peristaltic reflex.…”
Section: Discussionmentioning
confidence: 87%
“…Substances which stimulate sensory receptors in general, e.g. 5-HT, phenyl diguanide or S.R.KOTTEGODA 688 PERISTALTIC REFLEX substance P, when applied to the mucosa, stimulate peristalsis (Btilbring & Lin, 1958;Beleslin & Varagi6, 1958).…”
Section: Introductionmentioning
confidence: 99%
“…Substance P. when acting on the outside of the isolated guinea-pig ileum, blocks the peristaltic reflex (Beleslin and Varagic, 1959). In previous work some evidence was obtained that this block of peristalsis might be at least partly produced by the action of substance P on the intestinal ganglia.…”
mentioning
confidence: 99%
“…It is concluded that the potentiating effect of substance P on the response of the nictitating membrane to submaximal stimulation of the preganglionic sympathetic nerve is probably due to sensitization of acetylcholine receptors in the postsynaptic neurone. The present experiments do not explain how substance P potentiated the response to sympathomimetic amines.It has been shown that substance P may restore peristalsis when injected into the lumen of the isolated guinea-pig ileum in which the peristaltic reflex has been abolished by fatigue, by external or internal application of 5-hydroxytryptamine, or by lowering the temperature of the bath (Beleslin and Varagic, 1958). Substance P. when acting on the outside of the isolated guinea-pig ileum, blocks the peristaltic reflex (Beleslin and Varagic, 1959).…”
mentioning
confidence: 99%
See 1 more Smart Citation